Nachhaltigkeit und GIS: Räumlich differenzierende Nachhaltigkeitsindikatoren in kommunalen Informationsinstrumenten zur Förderung einer nachhaltigen Siedlungsentwicklung - Flacke, Johannes (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
The ongoing consumption of open space for settlement and traffic purposes is to be solved by integrating new economic control instruments as well as improved information instruments. The latter combined with spatially small-scaled indicators should be used in order to specify objectives of a sustainable settlement development and to bring these into practise. An example for this is given with the „Information System Sustainable Settlement Development”, a decision support system for the municipal planning process.